Penerapan Algoritma Genetika untuk Penjadwalan Mata Pelajaran - Ardiansyah, Hendri; Junianto, Mochammad Bagoes Satria (STMIK Budi Darma, 2022)
Scheduling of subjects in schools often has problems with the course of teaching and learning activities. There are various variations in this problem, due to differences in different policies in scheduling, at Lazuardi Global Compassionate School, Depok City, the schedule is made by making a rough description of the schedule and then transferring it to the Google Sheet application, scheduling in this way is still often mismatched. scheduling is made and also takes quite a long time. This causes the optimal scheduling difficult to obtain. This study discusses the application of genetic algorithms for scheduling subjects at Blue Blue Compassionate School Elementary School. Genetic algorithm is an algorithm that can solve problems in lesson scheduling and provide solutions to get optimal scheduling results. Based on the results of the tests carried out, the parameters used are the number of populations, the number of generations, crosses and mutations that the genetic algorithm can work well and solve problems by producing optimal scheduling and shorten the time of making the schedule so that the making of the schedule becomes effective and efficient.